Detection and effects of lack of fusion defects in Hastelloy X manufactured by laser powder bed fusion - Palm, M. S.; Diepold, Benedikt; Neumeier, Steffen; Höppel, Heinz Werner; Göken, Mathias; Zaeh, M. F. (Materials & Design, 2023)
Laser Powder Bed Fusion (L-PBF) is increasingly used for the manufacturing of complex metal parts. A major hurdle for L-PBF to manufacture critical parts is the lack of knowledge about the effects of inner material defects on the material properties. This paper presents a new method to manufacture specimens with inner lack of fusion (LOF) defects and to detect and localize them simultaneously by the in-process monitoring tool Optical Tomography (OT). The presence of defects at locations indicated by OT was verified through Computed Tomography analyses. Correlative metallographic preparation of the processed specimens showed LOF defects with their main extent within the build plane and sharp edges. Moreover, microstructural investigations revealed a fine globular grain structure and coarse dendritic segregations in the area, influenced by the defect. Correlations between the LOF defects analyzed in the microstructure and corresponding OT indications were established. Tensile tests and high cycle fatigue tests were performed on defective and non-defective material to evaluate the effects of LOF defects on the material properties of Hastelloy® X manufactured by L-PBF. While a minor influence of the LOF defects on static material properties was identified, the fatigue life of the defective specimens was significantly reduced.
Created from Fastlane, Scopus look-up
Keywords: Additive manufacturing; Effects of defects; Hastelloy X; High cycle fatigue; Laser powder bed fusion; Optical tomography